Reform Options for the Countercyclical Capital Buffer - Lukas Menkhoff (Wirtschaftsdienst)
Abstract The countercyclical capital buffer (CCyB) requires banks to hold certain equity capital depending on the state of the financial cycle. The role of this buffer is to stabilise the credit supply during the ups and downs of the financial cycle. Since its introduction in 2016, a discussion on reform options includes suggestions such as : (1) the buffer range should be increased to better counteract the financial cycle, (2) part of the buffer could be decided at the European level, (3) the buffer should lie at the midpoint of its range in normal times, and (4) the buffer requirement should be based on another rule-based component reflecting asset prices.